1980
DOI: 10.1099/00207713-30-1-129
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and Emended Description of Strains of Erwinia Isolated from Musa paradisiaca Linnaeus

Abstract: The phytopathogenic bacterium which causes soft rot of the pseudostem of Musa paradisiaca Linnaeus has been designated previously as Erwiriia carotovora subsp, paradisiaca, E. paradisiaca, E. carotovora subsp. chrysanthemi, and E. chrysanthemi. Thirty strains were examined and compared with strains of closely related Erwinia species and their subspecies. The strains from M. paradisiaca were found to be phenotypically similar to E. chrysanthemi strains on the basis of the following characteristics: pectate degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…paradisiaca by Dickey and Victoria (20) and Dye et al (26). These strains cause soft rot of the pseudostem of Musa paradisiaca.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…paradisiaca by Dickey and Victoria (20) and Dye et al (26). These strains cause soft rot of the pseudostem of Musa paradisiaca.…”
Section: Resultsmentioning
confidence: 97%
“…In the past, several authors have proposed subdivision of Erwinia chrysanthemi into four DNA homology groups (9), six phenotypic groups (17,20), or five serogroups (55,56). We could differentiate only two subphena.…”
Section: Resultsmentioning
confidence: 99%
“…The bacterial isolates were tested for the physiological and biochemical characteristics with regard to potato soft rot, gelatine liquefaction, sensitivity to erythromycin, indole production, phosphatase test, growth at 36 to 37 0 C. The tests were conducted as per the methods described by Dickey and Victoria (1980) and Dickey (1981).…”
Section: Biochemical Characteristicsmentioning
confidence: 99%
“…Lakshmanan and Mohan (1986) observed tip over disease or head rot caused by Erwinia carotovora in Tamil Nadu in North Arcot and Trichy districts. Dickey and Victoria (1980) reported that, the strain from M. paradisiaca in Colambia was very similar to E. chrysanthemi on the basis of biochemical and physiological properties. Snehalatharani and Khan, (2010) reported the bacterium showing positive for pectate degradation on CVP medium, growth at 36 0 C and 39 0 C, catalose production and negative for indole production.…”
Section: Introductionmentioning
confidence: 97%
“…In the case of pathogenic differences between the isolates, host specificity seems difficult to prove (Dickey, 1981;Janse and Ruissen, 1988). However, physiological (biochemical) testing revealed differences between E chrysanthemi strains (Hildebrand et al, 1978;Samson and Nassan-Agha, 1978; Dickey, 1979;Dickey and Victoria, 1980;Thomson et al, 1981).…”
Section: Introductionmentioning
confidence: 99%